(untitled) (Journal of Science and Technology, 2016)
Monitoring of adverse drug reaction (ADRs) has become an integral part of drug development and patient care. In most developing countries, however, ADR monitoring is virtually non-existent. Suggestions are offered for the setting up of a National Committee to initiate and oversee ADR monitoring in Ghana. The advantages of such systematic ADR monitoring are given. Problems that may hinder efforts to initiate and maintain ADR monitoring are reviewed and solutions suggested. It is hoped that the two Teaching Hospitals in Kumasi and Accra will take the lead in setting up ADR monitoring systems that would spread to involve most parts of the country.